"Lewend en kragtig"? Die hermeneutiese dinamika en implikasies van (her)interpretasie in die Ou Testament - Jonker, L (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
Biblical interpretation remains a contentious matter. Not only are there regularly fierce debates in church circles on how the Bible should be interpreted on issues of dogma and ethics, but even the letter columns of newspapers and chatrooms on the internet are often full of discussions on all aspects of biblical interpretation. These debates cover the whole spectrum of opinions ranging from those who insist on the factual accuracy and credibility of the Bible and who cling to this belief with a passionate conviction as a guide to doctrine and to life, to those who think that the Bible no longer has any value in a scientific age and that it should therefore be rejected as a source which has any authority. In these debates there is not much room for nuance. The conviction is expressed in this article that a study of how interpretation is undertaken in the Bible could open up important perspectives on the difficult questions of the interpretation of the Bible in our own time. In addressing the issue of interpretation in the Bible this article concentrates on the Old Testament, the field of specialisation in biblical scholarship of the author. The study starts with an overview of the research done in the discipline of Old Testament studies on the phenomenon of inner-biblical interpretation. In a subsequent section the phenomenon of inner-biblical interpretation is illustrated with reference to research on the books of Chronicles. This survey and the illustrations are followed by a section in which the hermeneutic implications of the dynamics of (re)interpretation in the Bible are spelled out for theology and the church. In the conclusion the article returns to the questions posed in the introduction.